2019
DOI: 10.2298/gsgd1902001l
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of torrential flood susceptibility: Case study - Ukrina River Basin (B&H)

Abstract: Torrential floods are the most frequent natural catastrophic events in the Republic of Srpska (B&H). The main objective of this study is susceptibility assessment to torrential floods in Ukrina River Basin using Index Based Method (IBM) and Flash Flood Potential Method (FFPI), which operates entirely in a GIS environment. The definition and identification of influencing factors for torrential floods was the first step in the process of developing the Torrential Flood Susceptibility Model (TFSM). According to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
5
0
2
Order By: Relevance
“…Susceptibility to torrential floods with this method was also analyzed in the region, Republika Srpska (B&H), for the Ukrina River Basin. In this basin, which covers an area of 1,498.81 km 2 , it was found that the class of very high susceptibility covers 9.65% of the basin area, high susceptibility category 31.21%, medium susceptibility occurs at 39.81% and low at 19.33% of the observed territory (Lovrić et al, 2019).…”
Section: Fig 2 Susceptibility Of the Mlava River Basin To Torrential Floodsmentioning
confidence: 80%
See 3 more Smart Citations
“…Susceptibility to torrential floods with this method was also analyzed in the region, Republika Srpska (B&H), for the Ukrina River Basin. In this basin, which covers an area of 1,498.81 km 2 , it was found that the class of very high susceptibility covers 9.65% of the basin area, high susceptibility category 31.21%, medium susceptibility occurs at 39.81% and low at 19.33% of the observed territory (Lovrić et al, 2019).…”
Section: Fig 2 Susceptibility Of the Mlava River Basin To Torrential Floodsmentioning
confidence: 80%
“…This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution-NonCommercial-NoDerivs 3.0 Serbia Увод Природно и антропогено изазване непогоде веома су честе у свету, и могу проузроковати велику материјалну штету и значајан губитак људских живота. Утврђивање обима и надокнада штете услед поплава је тешко спроводиво у пракси (Alcantara, 2002;Toya & Skidmore, 2007;Živković et al, 2015;Spalevic et al, 2017;Blöschl et al, 2019;Lovrić et al, 2019). Појава природних и антропогених екстрема (климатске промене, губитак биодиверзитета, прекомерна експлоатација природних ресурса) широм света наводи нас да обратимо већу пажњу на њихове утицаје на животну средину и економске активности (Guzzetti et al, 2005;Schmidt et al, 2006;Lerner, 2007).…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Globalization brings new challenges and imposes increasing demands on the quality of the environment (Gajić & Cvetanović, 2015;Menković et al, 2018;Lovrić et al, 2019). Human resources management involves the initiation of quality improvement initiatives, expressed through an adequate allocation and maximization of human resources.…”
Section: Introductionmentioning
confidence: 99%